TATA KELOLA KOTA PEKANBARU MENUJU SMART CITY MADANI - Wan Rahmah Yudin; Zaili Rusli SD (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
This research is motivated by the Pekanbaru City government which will apply the concept of Smart city Madani. That in the concept of Smart city Madani, the pillars are to realize the government in arranging the planning to be carried out.In running and realizing the City of Pekanbaru with the concept of Smart City Madani it is necessary to consider factors that support the realization of the program. One of the supporting factors is by conducting socialization to the public. Because socialization is an effort to communicate activities to create dialogue with the community. Through outreach will help to increase the understanding of the community and related parties about planned community empowerment programs and activities. Therefore, socialization is very necessary because many people in Pekanbaru still don't know about the government program. This research was arranged in a systematic frame of mind using a deductive model. The type and research approach used in this research is descriptive qualitative. Research informants numbered 3 (three) people. Data collection is carried out through observation, interviews and documentation which are then analyzed using qualitative analysis techniques. The study found that at the moment Pekanbaru City towards Smart City Madani has not been implemented well due to the lack of budget to realize the six (6) pillars towards Smart City Madani. But in optimizing the realization of Smart City Madani Pekanbaru City has six (6) priorities to accelerate the realization of Smart City Madani, namely: first, Pekanbaru SmartCard as a service card. Second, Simcard RT / RW Service. Third, Pekanbaru Command Center. Fourth, Data Center. Fifth, Pekanbaru Techno Park. Sixth, Emergency call services 112.Keywords: Governance, City of Pekanbaru, Smart City Madani.